Altered modulation of motor cortical excitability by electrical stimulation over the cerebellum in chronic migraine. Issue 1 (January 2019) - Centurioni, C.; Abagnale, C.; Di Lorenzo, C.; Parisi, V.; Pierelli, F.; Coppola, G.
Abstract : Previous structural neuroimaging studies suggest that patients with chronic migraine (CM) with and without medication overuse have abnormal structural changes within the cerebellum. In humans, cerebellum exerts a suppressive effect on the contralateral motor cortical response through a cerebello-thalamo-cortical pathway. We recruited 10 patients affected from CM without medication overuse and 10 heathy volunteers (HVs). After a conditioning single pulse high-voltage electrical stimulation delivered over the posterior surface of the mastoid processes, a TMS pulse was delivered over the contralateral motor cortex with 5, 7, 10, and 15 ms interstimulus interval (ISI) in random order. Motor cortical excitability changes were evaluated by amplitude changes of EMG responses from the FDI muscle to motor cortical stimulation. In HVs, suppression occurred at ISI of 5 ms and lasted few milliseconds. In CM patients, conditioning electric stimulation over the cerebellum did not reduce the size of MEPs to test TMS of the motor cortex at conditioning-test intervals of 5 ms. Here, we found neurophysiological evidence for dysfunctional cerebello-thalamo-cortical inhibitory pathway in CM. Whether these functional abnormalities are due to primary abnormal cerebellar inhibitory dysfunction or are secondary to a disrupted cerebellar-thalamic-cortical connectivity, remains to be determined.